2009
DOI: 10.1055/s-0029-1185536
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Isolation of Anti-InflammatoryC-Glucosylflavones fromPassiflora edulis

Abstract: Passiflora edulis, commonly known as "maracujá", is widely cultivated in Brazil for the industrial production of juice. The species of Passiflora are popularly used as a sedative or tranquillizer, and also against intermittent fever and skin inflammation. In this study we evaluated the anti-inflammatory activity of four sub-fractions and three isolated compounds from the butanolic fraction of P. edulis var. flavicarpa leaves, using the mouse model of pleurisy induced by carrageenan. The butanolic fraction obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 15 publications
0
35
0
5
Order By: Relevance
“…43 P. incarnata reportedly contains glycosyl flavonoids, 44,45 and P. edulis has antioxidant 46,47 and anti-inflammatory properties. 48,49 These properties may explain its effects on glycemia and the lipid profile in the animals we studied. The antioxidant compounds of P. edulis are 16 apigenin or luteolin derivatives, which include 4 mono-C-glycosyl, 8 O-glycosyl-C-glycosyl, and 4 O-glycosyl derivatives.…”
Section: -36mentioning
confidence: 99%
“…43 P. incarnata reportedly contains glycosyl flavonoids, 44,45 and P. edulis has antioxidant 46,47 and anti-inflammatory properties. 48,49 These properties may explain its effects on glycemia and the lipid profile in the animals we studied. The antioxidant compounds of P. edulis are 16 apigenin or luteolin derivatives, which include 4 mono-C-glycosyl, 8 O-glycosyl-C-glycosyl, and 4 O-glycosyl derivatives.…”
Section: -36mentioning
confidence: 99%
“…A recent review on the chemical constituents of the Lychnophorinae tribe has revealed significant variation in the occurrence of secondary metabolites in the genus Lychnophora [12]. Considering a single species, three phenomena can account for the observed differences: (a) accomplishment of a phytochemical investigation looking for a specific class of target secondary metabolites only, such as sesquiterpene lactones [13,14]; (b) performance of bioguided fractionation, which inspects a typical biological activity and may result in the isolation of a common class of secondary metabolites [15][16][17]; and (c) natural chemical variations in metabolism or presence of chemotypes [6][7][8]10].…”
Section: Introductionmentioning
confidence: 99%
“…ZUCOLOTTO e colaboradores, isolaram iso-orientina, vicenina-2 e spinosina da fração butanólica do extrato de Passiflora edulis, e atribuíram parte da atividade anti-inflamatória a estes compostos (ZUCOLOTTO et al, 2009 morte precoce e à outras patologias advindas da presença de patógenos no solo quando comparada às demais espécies tradicionalmente cultivadas (MENEZES et al, 1994, OLIVEIRA et al,1994, MELETTI e BRUCKNER, 2001, FISCHER, 2003 …”
Section: O Extrato Aquoso Dos óRgãos Aéreos Deunclassified
“…ZUCOLOTTO e colaboradores, isolaram iso-orientina, vicenina-2 e spinosina da fração butanólica do extrato de Passiflora edulis, e atribuíram parte da atividade anti-inflamatória a estes compostos (ZUCOLOTTO et al, 2009 Passiflora setacea é uma espécie de maracujá bastante utilizada no preparo de doces e sorvetes e é denominada popularmente por maracujá-sururuca, maracujá-do-sono, maracujá de cascavel (OLIVEIRA e RUGGIERO 2005). Porém esta espécie é pouco estudada, com quase nenhuma informação sobre sua composição química e efeitos medicinais.…”
Section: O Extrato Aquoso Dos óRgãos Aéreos Deunclassified
See 1 more Smart Citation